Enhanced nonlinear interactions in quantum optomechanics via mechanical amplification - Marc-Antoine Lemonde (Nature Portfolio, 2016)
Optomechanics harnesses the interaction between mechanical resonators and light, but weak matter–single-photon interactions limit studies to the linear regime. Here, the authors show that the interaction can be enhanced by modulating the spring constant of the resonator.